Application of Long Distance Communication for Corn Seed Drying Control and Monitoring Sistem - Hendra, Hendra (Faculty of Engineering, Universitas Tanjungpura, 2026)
The drying process of corn kernels, which primarily depends on solar energy, is significantly affected by unpredictable weather conditions, especially rainfall, leading to a decline in the quality of the harvested corn. This study aims to design and implement a long-range communication system for an Internet of Things (IoT)-based monitoring and control system for corn kernel drying. The developed system employs an ESP32 microcontroller as the transmitter to acquire data from the DHT11 temperature and humidity sensor and the rain sensor, as well as to control a DC motor through an L298N motor driver. Meanwhile, an ESP8266 microcontroller functions as the receiver, receiving data via the LoRa SX1278 communication module and transmitting it to the Thinger.io platform over the Internet. The system is capable of operating in both automatic mode based on sensor readings and manual mode through the Thinger.io dashboard. The communication performance parameters analyzed include the Received Signal Strength Indicator (RSSI), Signal-to-Noise Ratio (SNR), and communication delay at various testing distances. The experimental results indicate that the LoRa communication system performed successfully at communication distances of 100 m, 200 m, and 250 m. At a distance of 100 m, the average RSSI, SNR, and communication delay were −80.8 dBm, 3.5 dB, and 1800 ms, respectively. At a distance of 200 m, the average RSSI, SNR, and communication delay were −89.3 dBm, −5.625 dB, and 3000 ms, respectively. Although signal quality deteriorated with increasing communication distance, the transmitted data were still received reliably, enabling the monitoring and control system to maintain real-time operation.